CRUSADE: Is it still a good score to predict bleeding inacute coronary syndrome? - Bento, D. (2017)
Introduction: Major bleeding is a serious complication of acute coronary syndrome (ACS) andis associated with a worse prognosis. The CRUSADE bleeding score is used to stratify the risk ofmajor bleeding in ACS.Objective: To assess the predictive ability of the CRUSADE score in a contemporary ACS popu-lation.Methods: In a single-center retrospective study of 2818 patients admitted with ACS, the CRU-SADE score was calculated for each patient and its discrimination and goodness of fit wereassessed by the area under the receiver operating characteristic curve (AUC) and by the Hosmer-Lemeshow test, respectively. Predictors of in-hospital major bleeding (IHMB) were determined.Results: The IHMB rate was 1.8%, significantly lower than predicted by the CRUSADE score (7.1%,p<0.001). The incidence of IHMB was 0.5% in the very low risk category (rate predicted by thescore 3.1%), 1.5% in the low risk category (5.5%), 1.6% in the moderate risk category (8.6%),5.5% in the high risk category (11.9%), and 4.4% in the very high risk category (19.5%). Thepredictive ability of the CRUSADE score for IHMB was only moderate (AUC 0.73).The in-hospital mortality rate was 4.0%. Advanced age (p=0.027), femoral vascular access(p=0.004), higher heart rate (p=0.047) and ticagrelor use (p=0.027) were independent predictorsof IHMB.Conclusions: The CRUSADE score, although presenting some discriminatory power, significantlyoverestimated the IHMB rate, especially in patients at higher risk. These results questionwhether the CRUSADE score should continue to be used in the stratification of ACS.